Proyecto de Renovación en la Franja de Protección del Rincón de Girón, Santander. - Rivera Ruiz, Edwin Arturo (Universidad Antonio Nariño, 2023)
The Urban Renewal project in the protection strip located in the Poblado neighborhood of the municipality of San Juan de Girón, department of Santander, Colombia; It intends to strengthen the municipality between the neighborhoods of El Carmen and the Constituent Assembly on the La Isla sector. In the research analysis, the state of the environmental protection strip is concluded, which disobeys the proper use of occupation and has a bad perception of the space for citizens; Therefore, it seeks to improve the occupation of public space, the sustainable development of the sector through integration spaces focused on conservation and recreation on the strip.